THE ROLE OF EDUCATIONAL INSTITUTIONS IN TACKLING ONLINE GAMBLING EXPOSURE IN COLLEGE STUDENTS: AN EPA-BASED THERAPEUTIC APPROACH - Indasah, Indah; Safitri, Aizun Riski; Hartini, Ayu (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to analyze the relationship between the level of academic stress and religiosity towards the tendency of online gambling behavior among Indonesian university students. The phenomenon of increasing student involvement in online gambling practices indicates psychological and spiritual problems that need to be studied comprehensively. This study used a quantitative approach with a correlational survey method of 200 students from various public and private universities. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS software version 26. The results showed that academic stress had a significant positive effect on the tendency of online gambling behavior, while religiosity had a significant negative effect. The coefficient of determination (R²) value of 0.426 indicates that the two variables explain 42.6% of the variation in online gambling behavior. This finding confirms that the higher the academic stress of students, the greater their tendency to engage in online gambling, but a high level of religiosity is able to act as a protective factor against this behavior. This study recommends the need for a psychological and spiritually-based integrative counseling approach in higher education settings.